PC.12 Gender-specific effects on the development of white matter tracts in preterm babies. (9th June 2014) - Anblagan, D; Bastin, ME; Sparrow, S; Piyasena, C; Pataky, R; Moore, E; Wilkinson, G; Roberts, N; Semple, SI; Boardman, JP
Abstract : Introduction: Diffusion tensor imaging (DTI) may provide insights into cerebral changes associated with preterm birth by supplying biomarkers of white matter microstructure in tracts of interest (TOI). We used a tractography-based segmentation method, probabilistic neighbourhood tractography (PNT), 1, 2 to study gender-specific effects in developing white matter tracts in preterm infants. Methods: 49 preterm infants underwent DTI (3T MRI) comprising 11 T2- and 64 diffusion-weighted (b = 750s/mm 2 ) single-shot spin echo EPI volumes with 2 mm isotropic voxels at term-equivalent age. 10 TOIs were identified using PNT (http://www.tractor-mri.org.uk). 2 Using a neighbourhood of seed voxels, the seed point that produced the best matching tract to the reference (MNI standard space) was determined. The resulting tractography masks were applied to each subject's mean diffusivity (D) and fractional anisotropy (FA) maps, which permitted tract-averaged measures for each TOI. Results: Tract-averaged FA values of the left cingulum cingulate gyri (CCG) were significantly increased in male infants (p = 0.05), while (D) of the left CCG were significantly increased in female infants (p < 0.04). When the biomarkers were corrected for postmenstrual age at birth and scan, track averaged (D) of the left CCG was significantly increased (p < 0.03) in female infants (1551 ± 285 µm 2 /s) compared to male infants (1397 ± 858 µm 2 /s). Discussion: Quantitative DTI measures can be determined in TOIs in preterm brains using PNT. These values are comparable to other studies using tractography methods, and demonstrate increased diffusivities and reduced FA in CCG of female preterm infants compared with male equivalents. References: Clayden JD, et al . IEEE Trans Med Imaging 2007;26:1555–1561 Clayden JD, et al . J Stat Software 2011;44(8):1–18